Rola rad nadzorczych w systemie władzy przedsiębiorstwa - Jasiński, Bartosz (The Place of the Board of Directors in the System of Power of Present Corporation, 2008)
The article presents problems of place of the board of directors in the system of power of present corporation. The article defines formal and real competences of the board of directors. It shows problems of their functioning, it also presents the possibility of better use of this gremium for good of corporation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 67-74